Pembelajaran Transformasi Digital dan Pemberdayaan Kewirausahaan pada Anak Binaan Panti Asuhan Nur Ilahi Pontianak - Hapsari, Fadhilla Anindita; Juniwati, Juniwati; Marwan, Nayla Inayah; Ardhionova, Reyhan Davin; Badariah, Alya; Suryanita, Fitri Novianti (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
This program aims to empower assisted children who face challenges in entrepreneurship skills and digital literacy, by providing entrepreneurship training, digital marketing, handicraft skills, and digitalization of data administration to increase management efficiency. Implementation methods include structured practical skills training, continuing education through an entrepreneurial approach, as well as activities to increase awareness of gender equality through discussions and anti-discrimination campaigns. Consultations with orphanage management were also carried out to understand existing obstacles and identify needs in data management for assisted children, which were then implemented in the form of data digitization. Results from the program showed significant improvements in entrepreneurial skills, digital marketing abilities, and children's understanding of the importance of gender equality. In addition, this program succeeded in changing the data management system from manual to digital, speeding up the recording process, and increasing data security. Recommendations for development programs include the implementation of more interactive learning methods, such as group discussions that allow more direct involvement, as well as advanced entrepreneurship training that focuses on small business management, so that children are able to develop deeper and more sustainable business skills in the future.